Autism Spectrum Disorder and Mitochondrial Dysfunction: The Role of Mitochondrial Dynamics - Buchanan, Erin (Department of Molecular and Cell Biology, 2023)
Numerous genes and biological pathways are implicated in the aetiology of the neurodevelopmental disorder, autism spectrum disorder (ASD). Our research group reported that mitochondrial dysfunction was associated with ASD in South African children diagnosed with ASD using differential methylation and metabolomics studies. Propionyl-CoA Carboxylase Subunit Beta (PCCB) was differentially methylated in our cohort ASD study, and its dysregulation can lead to the accumulation of propionic acid. This links PCCB's function to a well-established animal model that uses sodium propionate (NaP) to study ASD in rats. This thesis aimed to i) examine ASD-associated mitochondrial dysfunction in a neuronal-like cell model using NaP and to investigate its effects on mitochondrial dynamics and morphology; ii) investigate the application of this in a South African ASD cohort by measuring differential methylation of essential genes involved in mitochondrial dynamics. Undifferentiated, neuronal-like SH-SY5Y cells were treated with NaP at 1.5mM, 3mM and 5mM to induce mitochondrial stress. The effects of NaP mitochondrial-induced stress were quantified using MTT and ATP assays. Transmission electron microscopy (TEM), using cryogenic techniques, was used to examine mitochondrial morphology by measuring nine parameters: area, area2 , form factor, area-weighted form factor, aspect ratio, perimeter, circularity, Feret's diameter and roundness. TEM images were analysed using Fiji/Image J. Mitochondrial DNA (MT-DNA) copy number and STOML2 expression were measured using RTqPCR, and these data were compared to TEM data. STOML2 was the most differentially methylated gene in our ASD cohort in our previous study. Differential methylation of six essential genes (DRP1, FIS1, MFN1, MFN2, OPA1, STOML2) involved in mitochondrial fusion and fission were examined using targeted next-generation bisulfite sequencing (tNGBS) between ASD and control participants in a South African cohort. Significance for all experiments was determined using unpaired t-tests, one-way ANOVA and correlation analysis (p< 0.05). SH-SY5Y cells treated with NaP showed mitochondrial dysfunction as reflected in changes in ATP levels and no changes in cell viability were observed except at 9mM NaP. In addition, NaP treatments led to significant changes in mitochondrial morphology with significant decreases in mitochondrial area, perimeter, form factor and Feret's diameter between NaP treatments and control and a significant increase in circularity. These changes in morphological data were supported by a significant increase in MT-DNA copy number at 5mM and significant decreases in STOML2 expression at all concentrations. Together, the TEM and expression data highlight the balancing act between mitochondrial fusion and fission, with increasing levels of fission occurring with increasing NaP concentrations. In the South African cohort, there were significant differences in methylation between the ASD group compared to controls at two CpG sites in MFN2, two CpG sites in STOML2 and one CpG site in FIS1 (significant increases) and two CpG sites in OPA1 (significant decreases). The increase in FIS1 and decrease in OPA1 methylation are consistent with this balancing act between mitochondrial fusion and fission in mitochondrial dysfunction in this cohort. These results suggest a potential link between mitochondrial dysfunction and the fluctuation in mitochondrial dynamics and morphology. The inclusion of TEM demonstrates its unique ability to visualise mitochondrial ultrastructure and the effect changes in mitochondrial dynamics have on morphology as opposed to only examining these changes through gene expression and metabolic assays. Although the exact relationship between the TEM and gene expression data could not be fully explained in this study, it highlights the need to explore further the relationship between mitochondrial dynamics, biogenesis and mitophagy in the context of ASD aetiology and neuronal development.